Minimizing Parenting Stress of Preschool Children’s Migrant Parents in China: Role of Family Socioeconomic Status, Perceived Social Support, and Psychological Resilience - Jinghui Zhao; Jiajia Gong; Jing Zhou; Xitong Ke; Yaqian Li; Minghui Lu (SAGE Open)
In China, with the continuous advancement of urbanization, the size of the migrant population has significantly increased along with the challenging environments faced by them, drawing widespread societal attention to the parenting stress experienced by young children’s migrant parents. However, research on the mechanisms underlying the factors influencing such stress remains scarce. Therefore, based on the ABCX model of family crisis, this study investigates the relationships and underlying mechanisms among family socioeconomic status (SES), perceived social support, psychological resilience, and parenting stress using a sample of 2,533 migrant parents of preschool children in Guangdong Province, China. The results indicate that family SES negatively predicts the parenting stress of migrant parents of preschool children in China. Additionally, perceived social support and psychological resilience play a sequential mediating role in the relationship between family SES and parenting stress. This study provides valuable insights for government departments, social service agencies, and migrant families in exploring strategies to alleviate the parenting stress of preschool children’s migrant parents.